Determination Key Of Dipterocarpaceae Family In Arboretum Lancang Kuning University - Ades Galingging; Ambar Tri Ratnaningsih; Ika Lestari Hutasuhut (Universitas Andi Djemma Palopo, 2022)
Key determination is one of the techniques used to identify and recognize tree species. Dipterocarpaceae is one of the tree families that has the highest number of species in Indonesia. This study aims to identify the species of Dipterocarpaceae present in theArboretum and make a key of determination. The method used in this research is to carry out a census of Dipterocarpaceae species starting from the seedling, sapling, pole and tree levels, determine the coordinates of the Dipterocarpaceae species, take a sample of several leaf twigs of Dipetrocarpaceae species, document the samples taken for make a determination key based on leaf morphology. The results showed that there are currently 32 species of Dipterocarpaceae consisting of seedlings, saplings, poles and trees, which belong to 8 genera namely Anisoptera, Cotylelobium, Dryobalanops and Hopea there is 1 species, Dipterocarpus and Vatica 2 species, Parashorea there are 2 species, Shorea there a re 21 species and. For the determination key, there are 20 stages in the manufacture for the clanShoreawhereas forNon Shorea 10 steps were used to make the key of determination, this stage was made from the morphology of the leaves in each Dipterocarpaceae species.